Análise estrutural de um reservatório em concreto armado por método dos elementos finitos - Almeida, Alice Costa de (Universidade Federal Rural do Semi-Árido, 2019)
This paper presents an approach of a parallelepiped reservoir project in reinforced concrete, used in water storage, through the finite element method. The choice of numerical method used is based on more accurate validations of results and imposed requirements governed by the standards, such as tightness, safety and durability; crucial factors in the formation of cracks. By performing a simulation with the 2000®V19 software, in different mesh discretization until a convergence of its results. Analyzing the connection between the wall and the bottom slab and checking the Brazilian standard and the European standard in a quantitative way for the purpose of verifying the state of crack opening, comparing its peculiarities and imposed considerations. Where, we obtain different values between standards due to the consideration of the concrete drawn according to the results obtained in the mesh convergence.
Keywords: Reservatório; Análise; Fissuração; Verificação; Reservoir; Analyze; Cracking; Verification; ENGENHARIAS::ENGENHARIA CIVIL